2019
DOI: 10.2147/prbm.s165114
|View full text |Cite
|
Sign up to set email alerts
|

<p>Eating disorders among Moroccan medical students: cognition and behavior</p>

Abstract: Introduction and aimEating disorders (EDs) are complex, multifactorial diseases linked to biological, developmental, psychological, and sociocultural factors. Medical students are among subjects at high risk of EDs. The aim of the present investigation was to evaluate EDs among 710 Moroccan medical students with a focus on cognition and behavior related to EDs.MethodsSociodemographic, economic, and clinical data were collected. Validated questionnaires, such as the SCOFF (Sick, Control, One Stone, Fat, Food) q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
2
16
0
2
Order By: Relevance
“…3 Furthermore, a study conducted among 710 medical students in Morocco reported a prevalence of 32.8%. 4 In Malaysia, a study conducted among 279 medical students reported prevalence of eating disorder, which was 42.7%, 5 meanwhile, another study among 263 medical students found that 11% of the students were at risk of developing eating disorder. 6 Several risk factors are associated with eating disorder, including individual self-perception on ideal body weight and the influence of family members, peers, and the media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Furthermore, a study conducted among 710 medical students in Morocco reported a prevalence of 32.8%. 4 In Malaysia, a study conducted among 279 medical students reported prevalence of eating disorder, which was 42.7%, 5 meanwhile, another study among 263 medical students found that 11% of the students were at risk of developing eating disorder. 6 Several risk factors are associated with eating disorder, including individual self-perception on ideal body weight and the influence of family members, peers, and the media.…”
Section: Introductionmentioning
confidence: 99%
“…6 Individuals with self-perception of overweight body and having a high BMI were found to have symptoms of eating disorder. 4 Among normal weight adolescents, 53.3% felt their weight was not normal. 11 The desire to lose weight is a strong predictor of eating disorder as well.…”
Section: Introductionmentioning
confidence: 99%
“…EAT-8 is the short form of EAT-26. [ 33 ] It is an 8-item self-report tool which assesses problematic eating and is scored through two-item format (approximately agree[ 1 ], and approximately disagree [0]). Reliability and validity of questionnaire were reported desirable.…”
Section: Methodsmentioning
confidence: 99%
“…Eating disorders are complicated and multifactorial diseases which are related to various parameters such as biological, growth, psychological, and sociocultural factors. [ 1 ] Eating disorders are considerably correlated with psychological and physical disorders[ 2 ] and are associated with increase in mortality[ 3 ] and suicide[ 4 ] and impose significant financial burden on the health system. [ 5 ] Mortality rate for these patients is higher than patients with other psychiatric diseases,[ 6 ] and it is estimated that it is responsible for 12 times greater rate for other causes in women aged 15–45 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation